Diversity and Distribution of articulated Coralline algae (Rhodophyta, Corallinales) of the Atlantic coast of Mexico - Mendoza González, A. Catalina; Mateo-Cid, Luz Elena; García López, Deisy Yazmin; Acosta-Calderón, Julio Adulfo (Phytotaxa, 2014)
This paper provides the first critical revision of the articulated coralline algae Amphiroa and Jania along the Atlantic coast of Mexico and Mexican Caribbean, based on morphological and anatomical characters of numerous specimens both genera. We found six species of Amphiroa, including one new record for this region: Amphiroa valonioides. In the other hand, Amphiroa fragilissima and A. rigida have the wider distribution along the Atlantic coast of Mexico. Jania to encompass six species, J. capillacea and J. cubensis are the best represented along the Atlantic coast of Mexico. Male and female reproductive structures of several species are recorded for first time in the study area. The distribution of A. valonioides and A. vanbosseae seems to be the warm temperate and tropical coast of the Atlantic and Pacific Ocean. Macro and microscopic characteristics and relevant photographs and descriptions are provided for each species. Data on the distribution of taxa along the Atlantic and Caribbean coast of Mexico are included.